PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI - Ramadhan, M. Agil; Suryadi, Nanang (Jurnal Kewirausahaan dan Inovasi, 2023)
This study aims to determine the effect of work motivation and job satisfaction on performance in employees of the Kediri District Trade Office. The variables of this study are work motivation (X1), job satisfaction (X2) and employee performance (Y). This study used a quantitative method using data collection techniques in the form of interviews, observation, literature and questionnaires. While the analysis used is the validity test, reliability test, classic assumption test, multiple linear regression test, t test and f test and the coefficient of determination. Sampling in this study used a saturated sample with the consideration of all employees of the Kediri Regency Trade Office, totaling 57 employees based on the results of the research conducted. The results of this study indicate that partially work motivation influences employee performance and partially job satisfaction influences employee performance. This study also shows the results that simultaneously work motivation and job satisfaction affect employee performance.